2021
DOI: 10.1016/j.devcel.2021.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironmental interactions of oligodendroglial cells

Abstract: Developmental myelination is a protracted process that extends well into postnatal life. Cell-intrinsic mechanisms operate in myelin-forming oligodendrocytes, as well as microenvironmental interactions that guide and modulate every aspect of myelination, from oligodendrocyte precursor cell migration to oligodendrocyte differentiation and the formation of stable myelin internodes. During development and throughout adult life, neuron-oligodendroglial interactions shape activity and experience-dependent myelin ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 105 publications
(148 reference statements)
1
6
0
Order By: Relevance
“…In addition to electrical activity, developmental myelination depends on the crosstalk with other glial cells, astrocytes ( Dutta et al, 2019 ; Yalcin and Monje, 2021 ) and particularly microglial cells ( Santos and Fields, 2021 ). Chmr1, the receptor mediating clemastine-effect in OLs, is also expressed in microglia, as reported from previous RNAseq analysis ( Figure 5A ; Zhang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to electrical activity, developmental myelination depends on the crosstalk with other glial cells, astrocytes ( Dutta et al, 2019 ; Yalcin and Monje, 2021 ) and particularly microglial cells ( Santos and Fields, 2021 ). Chmr1, the receptor mediating clemastine-effect in OLs, is also expressed in microglia, as reported from previous RNAseq analysis ( Figure 5A ; Zhang et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that oligodendrocytes are of paramount importance in brain functions ( De Faria et al. 2021 ; Yalçın and Monje 2021 ; Munyeshyaka and Fields 2022 ). We consider it highly likely that future work on these cells will lead to important findings on the roles of oligodendrocytic NKCC1 in CNS development, plasticity, and disease (see also Castelijns et al.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to OLs, the balance of a healthy glial cell population is crucial to myelin development, homeostasis, and plasticity. 4,32 A certain subset of microglia populating axon tracts promotes myelination during brain development. Astrocytes influence myelin thickness and nodal gap length via thrombin protease secretion.…”
Section: Myelination and Glial Cell-mediated Phagocytosis In Developm...mentioning
confidence: 99%